Batyar Songs in Viktor Morozov’s Creativity: ДО 70-РІЧЧЯ МУЗИКАНТА - Oliinyk, Ivanna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The batyar subculture has already become the subject of many scientific works of Polish and Ukrainian researchers as a social phenomenon with its own jargon and cultural traditions. In particular, this issue has become central in the works of U. Jakubowska, A. Kozytsky, O. Kharchyshyn, Y. Vynnychuk, N. Kosmolinska, W. Szolginia and others. Batyar songs as a layer of Lviv city music got a new life thanks to the creativity of V. Morozov, realized in the publication of three albums with neobatyar songs. This group of songs and its genre and intonation parameters have not yet been at the center of musicological research and open up new perspectives for learning of genetic links between urban music and popular contemporary music in Ukraine. The purpose of the study is to analyze the genre and intonation features of Viktor Morozov’s albums, the principles of their cyclization, to explore the genetic links between batyar and neobatyar songs. Results and conclusions. Each of the three albums “Only in Lviv” (“Tilku vi Lvovi”), “Heart of the batyar” (“Serdtse batiara”) and “Batyarsky blues” (“Batiarskyi bliuz”) reveals itself as a large genre, which structure builds an expanded musical dramaturgy. In many aspects, it is connected with principles of the cyclization of academic genres, in particular, the vocal cycle and the program suite. The basis of the dramaturgy development of the albums was the method of contrast at the level of thematic, genre, tempo-metric organization. In addition, all three albums actually formed the one line of transformation of batiar songs from the authentic sound of songs from the period of the 20–30s of the twentieth century, and to new author’s — neobatyar songs, there were created on the basis of modern genres. New plots and themes of the verbal text of neobatyar songs also directly appeal to the original period of the first Lviv batyars at the beginning of the 20th century. The love adventures of the batyars, the struggle for authority and respect among the representatives of the subculture, the love for the native city, the glorification of fearlessness, life with not burdened by laws and fear became the main topics in neobatyar songs too. A characteristic local dialect is preserved, including a combination of vocabulary of various language systems; the use of lexical distortions, obscene vocabulary takes on a new embodiment through modern neologisms, borrowings. Songs are still performed exclusively by men, and the main genre outline is dance, including polkas, waltzes, tango, staer and others. The phenomenon of the double nature of batiar songs is organically embodied, where folklore and author’s songs are expressed through a combination of anonymous and original songs of the prewar period and neobatyar songs created by the authors of the albums. The nebatyars headed by V. Morozov in the albums “Only in Lviv”, “Heart of the batyar” and “Batyar blues” deliberately appeal to the layer of batyar songs, aiming to give new life to the old batyar song genre in the context of modern musical trends, to save the unique phenomenon from oblivion, rethink them in the context of the realities of our time. Thanks to the conceptual approach to the creation of the aforementioned albums, the authors managed not only to organically continue the musical traditions of batyar songs, but also to give them new life at a fresh, even brighter artistic level.